2015
DOI: 10.1002/app.42506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimicrobial, and release behaviors of tetracycline hydrochloride loaded poly (VInyl alcohol)/chitosan/ZrO2 nanofibers

Abstract: Tetracycline hydrochloride loaded poly (vinyl alcohol)/chitosan/ZrO 2 (Tet-PVA/CS/ZrO 2 ) hybrid nanofibers were fabricated via electrospinning technique. The representative weight ratio of PVA/CS at 3 : 1 was chosen to fabricate drug carrier PVA/CS/ ZrO 2 nanofibers. The drug carrier showed a decrease in average diameter with the increase of ZrO 2 content at given conditions, and the nanofibers were uneven and interspersed with spindle-shape beads with ZrO 2 content at 60 wt % and above. The networks linked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Electrospinning is a simple and inexpensive dry spinning process based on the use of charged droplets that draw micro/nano scale fibers from a liquid polymer solution or a melt [5]. The large interest in electrospinning is justified by its various advantages such as high surface-to-volume ratio, tunable porosity and simplicity of surface functionalization [7,8]. 8. collecting screen (rotary or stationary) 9. fibers) [6] Polymers Used in Electrospinning…”
Section: Fundamentals Of Electrospinning Processmentioning
confidence: 99%
“…Electrospinning is a simple and inexpensive dry spinning process based on the use of charged droplets that draw micro/nano scale fibers from a liquid polymer solution or a melt [5]. The large interest in electrospinning is justified by its various advantages such as high surface-to-volume ratio, tunable porosity and simplicity of surface functionalization [7,8]. 8. collecting screen (rotary or stationary) 9. fibers) [6] Polymers Used in Electrospinning…”
Section: Fundamentals Of Electrospinning Processmentioning
confidence: 99%
“…Previously, some of us have reported that when PVP was present in fibers, it facilitated the release of the sparingly water-soluble drug curcumin from polylactide- and CA-based electrospun fibrous materials [ 17 , 18 ]. Drug-loaded fibrous materials with incorporated PVP or PVA have been shown have prospects for use in biomedical applications [ 19 , 20 , 21 , 22 ]. Such systems have been reported to exert good antioxidant, antimicrobial, anticancer and/or wound-healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning of PVA is easily feasible. PVA-based fibrous materials have been demonstrated to be promising in terms of applications in biomedicine [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%